Histone Acetyltransferases and Deacetylases Are Required for Virulence, Conidiation, DNA Damage Repair, and Multiple Stresses Resistance of Alternaria alternata - Ma, Haijie; Li, Lei; Gai, Yunpeng; Zhang, Xiaoyan; Chen, Yanan; Zhuo, Xiaokang; Cao, Yingzi; Jiao, Chen; Gmitter, Fred G.; Li, Hongye (Frontiers in Microbiology, 2021)
Histone acetylation, which is critical for transcriptional regulation and various biological processes in eukaryotes, is a reversible dynamic process regulated by HATs and HDACs. This study determined the function of 6 histone acetyltransferases (HATs) (Gcn5, RTT109, Elp3, Sas3, Sas2, Nat3) and 6 histone deacetylases (HDACs) (Hos2, Rpd3, Hda1, Hos3, Hst2, Sir2) in the phytopathogenic fungus Alternaria alternata by analyzing targeted gene deletion mutants. Our data provide evidence that HATs and HDACs are both required for mycelium growth, cell development and pathogenicity as many gene deletion mutants (ΔGcn5, ΔRTT109, ΔElp3, ΔSas3, ΔNat3, ΔHos2, and ΔRpd3) displayed reduced growth, conidiation or virulence at varying degrees. In addition, HATs and HDACs are involved in the resistance to multiple stresses such as oxidative stress (Sas3, Gcn5, Elp3, RTT109, Hos2), osmotic stress (Sas3, Gcn5, RTT109, Hos2), cell wall-targeting agents (Sas3, Gcn5, Hos2), and fungicide (Gcn5, Hos2). ΔGcn5, ΔSas3, and ΔHos2 displayed severe growth defects on sole carbon source medium suggesting a vital role of HATs and HDACs in carbon source utilization. More SNPs were generated in ΔGcn5 in comparison to wild-type when they were exposed to ultraviolet ray. Moreover, ΔRTT109, ΔGcn5, and ΔHos2 showed severe defects in resistance to DNA-damaging agents, indicating the critical role of HATs and HDACs in DNA damage repair. These phenotypes correlated well with the differentially expressed genes in ΔGcn5 and ΔHos2 that are essential for carbon sources metabolism, DNA damage repair, ROS detoxification, and asexual development. Furthermore, Gcn5 is required for the acetylation of H3K4. Overall, our study provides genetic evidence to define the central role of HATs and HDACs in the pathological and biological functions of A. alternata.